Adherence to lifelines diet is associated with lower lung cancer risk in 98,459 participants aged 55 years and above: a large prospective cohort study - Shi, Yangpiaoyi; Xin, Li; Peng, Linglong; Xu, Zhiquan; Liu, Hang; Wei, Qi; Tan, Wanhao; Wang, Yaxu; Xiang, Ling; Gu, Haitao (Frontiers in Nutrition, 2024)
Background: Lifelines Diet Score (LLDS) was developed based on the 2015 Dutch Dietary Guidelines and current international scientific evidence. As a dietary quality assessment tool, the LLDS aims to evaluate the association between the Lifeline diet and the risk of chronic diseases. However, the evidence linking LLDS to lung cancer risk is currently limited. Objective: Our objective was to explore whether adherence to the LLDS is associated with reduced incidence and mortality of lung cancer, including its major histological subtypes: small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC). Methods: Data for this research were sourced from the Prostate, Lung, Colorectal, and Ovarian (PLCO) Trial. The LLDS for each participant was calculated based on responses to the dietary history questionnaire (DHQ), and subsequently analyzed after being categorized into quintiles. The Cox proportional hazards regression model was utilized to compute the hazard ratios (HRs) and 95% confidence intervals (CIs) for both the incidence and mortality of lung cancer, SCLC and NSCLC. Additionally, stratified analyses were conducted to ascertain possible effect modifiers, and several sensitivity analyses were performed to evaluate the robustness of the findings. Results: During the mean follow-up periods of 8.8 years for incidence and 15.1 years for mortality, we identified 1,642 new cases and 1,172 related deaths from lung cancer. Participants in the highest quartiles of LLDS compared to those in the lowest exhibited a reduced incidence (HR Q4:Q1 = 0.80, 95% CI = 0.68-0.94, P for trend = 0.003) and mortality (HR Q4:Q1 = 0.81, 95%CI = 0.67-0.98, P for trend = 0.009) of lung cancer. Furthermore, this negative association remained for SCLC incidence (HR Q4:Q1 = 0.55, 95% CI = 0.35-0.87, P for trend = 0.002) and mortality (HR Q4:Q1 = 0.42, 95% CI = 0.25-0.70, P for trend < 0.001). The association between LLDS and the incidence and mortality of lung cancer is not influenced by pre-defined potential effect modifiers (all P interaction > 0.05). The sensitivity analyses substantiated the robustness of the results. Conclusion:our research indicates that adherence to the LLDS is linked to a diminished incidence and mortality of lung cancer.